Efficacy and safety of simultaneous combined Zephyr and Spiration valve therapy in patients with advanced pulmonary emphysema - Dittrich, A. Susanne; Kontogianni, Konstantina; Unterschemmann, Ann-Sophie; De Rossi, Susanne; Trudzinski, Franziska; Brock, Judith; Gompelmann, Daniela; Heußel, Claus Peter; Herth, Felix; Eberhardt, Ralf (Respiratory medicine, 2024)
Background - Endoscopic lung volume reduction with valves is a minimally invasive treatment strategy for patients with severe pulmonary emphysema. Two valve systems are currently available: Zephyr and Spiration valves. As these can be implanted simultaneously in the same procedure, the question arose as to the effect on lung function, exercise capacity and subjective disease perception after combined valve treatment. - Methods - We conducted a retrospective analysis of 108 patients with combined, simultaneous treatment of Zephyr and Spiration valves. The decision on which and how many valves to implant was based on the individual patient anatomy. Effects on lung function, exercise capacity and atelectasis formation as well as complications were evaluated 90- and 180-days post-treatment (90d-FU and 180d-FU). - Results - At 90d-FU (n = 90), the mean change was 86.7 ± 183.7 mL for FEV1 and -645.3 ± 1276.5 mL for RV, with responder rates of 39.8 % and 46.5 %, respectively. Complete atelectasis occurred in 16.7 % and partial atelectasis in 25.5 % of patients. Six-minute walking distance increased by 27.00 m [-1.50 - 68.50m]. The rates of pneumothorax (10.2 %) 6 months after treatment were not higher than in randomized controlled trials (RCTs). Likely due to the inclusion of high-risk patients, there was a higher incidence of severe COPD exacerbation (21.3 %) and pneumonia (12.0 %) compared to RCTs. - Conclusions - The combined implantation of Zephyr and Spiration valves resulted in significant clinical and functional improvements with an acceptable risk profile. Therefore, the ability to combine both valve types in severe emphysema could be a promising option in endoscopic lung volume reduction.